The internationalization of a family business group: The ownership, the leadership and the importance of the socio-emotional wealth dimensions. (9th October 2017) - Della Piana, Bice; Vecchi, Alessandra
Abstract : Purpose: The purpose of this paper is to provide some illustrative evidence to understand the distinctive forms of governance implemented by a well-established family business group (FBG) and to highlight the relative importance given to the different dimensions of socio-emotional wealth (SEW) during the internationalization process. Design/methodology/approach: Drawing on multi-level and longitudinal data, the research provides in-depth insights into how the affiliated firms are linked to the focal firm, how the founding family in a large FBG organizes the top leadership roles spanning multiple countries and whether the inter-organizational and inter-personal networks changes over time and which are the most important items representing the SEW dimensions. Findings: From the findings, it emerges that family ownership, family leadership and the presence of trusted people as pivotal actors in the FBG's internationalization process. Originality/value: The originality of the research stems from its contribution because despite providing illustrative evidence based on a single case-study, the findings offer additional insights over the importance of and the instrumental role played by SEW preservation as a perspective to explain FBGs' internationalization.